(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2023)
Differentiated thyroid carcinoma (papillary and follicular) is the most frequent endocrine neoplasia, but it only occupies 1% of all cancers and of this small percentage only present atypical distant metastases in approximately 5 to 10%. It is an impressive manifestation of cancer in general, especially in an advanced stage and long evolution, aggressive histological variety, which implies a worse prognosis, the diagnosis is based on the images obtained (gold standard) by magnetic resonance or computed tomography Two cases of advanced or vultuous thyroid carcinoma that presented ocular and cerebral metastases respectively, their clinical presentation, diagnosis and treatment are presented. Being an infrequent or rare manifestation of papillary thyroid carcinoma, which makes the cases interesting.